Theoretical analysis of the processes of the simultaneous wastewater treatment from the organic contaminants and nitrogen compounds using of the biofilm models - Oliynyk, O.Ya.; Telyma, S.V.; Kalugin, Yu.I.; Oliynyk, Ye.O. (Reports of the National Academy of Sciences of Ukraine, 2023)
The mathematical models and the parameter calculations of the simultaneous wastewater treatment from the organic contaminants and ammonium nitrogen compounds in the bioreactors-aerotanks with additional fixed biocenosis as a biofilm in their volume are proposed. The questions connected with the heterogeneous structure of biofilm from different bacteria and the substantiation of the balance equations system with kinetic reactions for following their realization which is describing the simultaneous removal OC and N in biofilm taking into account the oxygen regime O2 are considered. As a result of the realization of the created models taking into account the influence of the different factors on the simultaneous wastewater treatment from OC and N processes the recommendations for parameter calculations are proposed. Besides the boundary conditions of necessary bacteria presence at which the simultaneous removing of the OC and N have occurred and at which conditions some of the substrates will limit the wastewater treatment processes are determined.